2020
DOI: 10.48550/arxiv.2007.10209
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Modified log-Sobolev inequalities, Beckner inequalities and moment estimates

Radosław Adamczak,
Bartłomiej Polaczyk,
Michał Strzelecki

Abstract: We prove that in the context of general Markov semigroups Beckner inequalities with constants separated from zero as p → 1 + are equivalent to the modified log Sobolev inequality (previously only one implication was known to hold in this generality). Further, by adapting an argument by Boucheron et al. we derive Sobolev type moment estimates which hold under these functional inequalities.We illustrate our results with applications to concentration of measure estimates (also of higher order, beyond the case of … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…Independently and, in a sense, in parallel with us Adamczak, Polaczyk and Strzelecki [1] have very recently obtained (among many other results) moment estimates and concentration bounds for Poisson functionals, which are similar to the ones we prove, see especially Section 4.7 in [1]. The main difference to their paper is that they use a so-called Beckner-type inequality as their starting point (a device we will be able to recover from our results as well, see Corollary 3.4), while we are building on a modified Φ-Sobolev inequality.…”
Section: Introductionmentioning
confidence: 91%
“…Independently and, in a sense, in parallel with us Adamczak, Polaczyk and Strzelecki [1] have very recently obtained (among many other results) moment estimates and concentration bounds for Poisson functionals, which are similar to the ones we prove, see especially Section 4.7 in [1]. The main difference to their paper is that they use a so-called Beckner-type inequality as their starting point (a device we will be able to recover from our results as well, see Corollary 3.4), while we are building on a modified Φ-Sobolev inequality.…”
Section: Introductionmentioning
confidence: 91%
“…for any functions f, g on Ω κ (which is the Dirichlet form of the underlying Markov chain). Recently, in [APS20] it was shown that in the context of general Markov semigroups, Beckner inequalities with constants bounded away from zero as p ↓ 1 and modified log-Sobolev inequalities are equivalent. In their article, the authors provide numerous examples and applications, also briefly discussing the multislice.…”
Section: Proof Using Convexity In the First Step And The Inequality (Amentioning
confidence: 99%